Virtual‐coordinate‐based delivery‐guaranteed routing protocol in three‐dimensional wireless sensor networks. Issue 2 (4th December 2012) - Liu, Bing‐Hong; Pham, Van‐Trung; Hou, Bo‐Yu; Chiu, Shih‐Wei
Abstract Because of the wide range of applications, many geographic routing protocols have been proposed in three‐dimensional (3D) wireless sensor networks. However, all the methods require assistance from a global positioning system (GPS), which is not always available. In this paper, we propose a method of constructing an axis‐based virtual coordinate assignment in 3D wireless sensor networks (ABVCap_3D) that requires no GPS assistance. We also propose a routing protocol based on ABVCap_3D, which guarantees packet delivery in 3D networks. Using simulations, we evaluate the performance of ABVCap_3D routing and other well‐known routing protocols, such as greedy‐random‐greedy routing, greedy‐hull‐greedy routing, and the routing based on axis‐based virtual coordinate assignment in 2D wireless sensor networks (ABVCap routing). Simulations show that ABVCap_3D routing requires significantly relative lower cost for guaranteeing packet delivery in comparison with ABVCap routing. Simulations also demonstrate that ABVCap_3D routing ensures a moderate ratio for routing path length to the shortest (ideal) path length. Copyright © 2012 John Wiley & Sons, Ltd.